“O bedel do Lyceu desempenha bem o seu lugar” – um olhar sobre os bedéis da Parahyba do Norte (1836-1889) - Lira, Vanessa Gonçalves (2022)
This is a dissertation that aims to understand the position of bedel at the Lyceo da Parahyba do Norte. To this end, our sources are the statutes of the school in the years 1837, 1846 and 1886, the Eighteenth-century legislation on public instruction and handwritten bureaucratic documents collected in the Historical Archive Waldemar Bispo Duarte - Funesc. The time frame chosen for this study is from 1836 to 1889, the initial mark being the year in which the position of bedel was created in the Parahyba secondary school and the final one the last mention of such occupation in the Paraiban press. We have worked on the organization of public education based on its employees and we understand that there was an organization in the disciplinary system of power in which the bedel was the protagonist about school discipline. We have seen the difference between position, function and subject. The position is the title of the job, the function the obligations to be fulfilled and the subjects were the people who made or did not make the rules be followed. We concluded that the position of bedel was intended to maintain order in the Lyceo. However, when we deal with the subjects we find distinctions of social places namely: Gervazio Victor da Natividade was a bedel, lieutenant and Pernambuco print journalist, Laurindo Peregrino Bandeira de Mello, bedel and elementary school teacher and Joaquim Pavão de Vasconcellos, bedel and ensign.